The hero - Carr, Robyn (Don Mills, Ontario : Harlequin MIRA, 2013)
Devon McAllister flees danger with her daughter and ends up in Thunder Point, Oregon, where she meets widowed father Spencer Lawson, a man who can teach her about safety and stability.
"Harlequin MIRA romance"--Spine.
Keywords: Man-woman relationships -- Fiction; Mothers and daughters -- Fiction; Single fathers -- Fiction; Oregon -- Fiction; Love stories